Film at the Crossroads of Narrative and Dramatic Genre - Bello, Maria do Rosário Leitão Lupi (VIA PANORAMICA: Revista de Estudos Anglo-Americanos / A Journal of Anglo-American Studies, 2019)
If film is a form of visual art, why does it rely mainly upon narrative text and is not more indebted to drama? Why are theatrical plays not so easily (and frequently) adapted for the screen as novels and short stories? Is it true, as Käte Hamburger suggests, that “filmed drama becomes epic”? In order to grasp the concept of film hybridism (both film theorists and film makers have long dealt with the natural tendency of film to absorb other art features and forms), in this paper I intend to address the issue of film genre by taking into account Jauss’s evolutional theory and confronting it with Frye’s concept of “radical of presentation”. André Bazin spoke of the impurity of film, whilst Manoel de Oliveira, who has been said to produce “theatrical films”, clearly states that “film adds to theatre the capacity of fixing the image in time”. Time is, in fact, a decisive factor in genre definition – as Hegel clearly demonstrated – and it is through the way that film deals with this factor that we are able to gauge either its distance from or its closeness to drama and/or to literature.